Business Driven Information Systems - Phillips Amy; Baltzan Paige (American : McGraw -Hill, 2007)
The Baltzan and Phillips approach in Business Driven Information Systems discusses various business initiatives first and how technology supports those initiatives second. The premise for this unique approach is that business initiatives drive technology choices in a corporation. Therefore, every discussion addresses the business needs first and addresses the technology that supports those needs second. This approach takes the difficult and often intangible MIS concepts, brings them down to the student's level, and applies them using a hands-on approach to reinforce the concepts. BDIS provides the foundation that will enable students to achieve excellence in business, whether they major in operations management, manufacturing, sales, marketing, etc. BDIS is designed to give students the ability to understand how information technology can be a point of strength in an organization. --This text refers to the Paperback edition.
Keywords: Industrial Management; Information technology